Examining Employee Perceptions of External Corporate Social Responsibility Initiatives in the Nepalese Banking Sector: A Descriptive Analysis - Yonghang, Yangsang (Nepal Journal of Multidisciplinary Research, 2023)
The study aimed to explore employee perceptions of external corporate social responsibility (CSR) activities in the Nepalese banking sector. The study used a descriptive research design and collected primary data using questionnaires distributed to employees of commercial banks in Nepal. A real sample was used, and the sample size was 40 participants. The study results show that employees have a positive perception of their company's external CSR efforts, including charitable contributions and environmental initiatives. Importantly, demographic factors like gender, marital status, age, years of service, and education do not significantly influence these perceptions. Thus, the organization’s commitment to external CSR appears consistent across diverse employee demographics. Future researchers can explore the relationship between employees' active involvement in CSR activities, such as volunteering, and their perceptions of the company's CSR commitment.